Hybrid scheduling approach for concurrent task execution on microcontroller-based systems - Nuru DASHDAMIRLI (Revista Română de Informatică și Automatică)
Microcontrollers are low-power, energy-efficient integrated circuits that contain a processor, memory, storage, and input/output peripherals in an all-in-one package. They are one of the most used components in embedded systems, both for consumer electronics and industrial machines. They have a wide range of applications, from simple tasks like controlling household appliances to complex systems such as space exploration equipment. As microcontrollers have limited resources available and are harder to program compared to general-purpose computers, concurrency is a challenging task to achieve in this domain. This paper proposes a new hybrid scheduling approach for achieving concurrency in microcontroller-based systems with the usage of virtual machines. The impact of this hybrid scheduling approach on resource utilization and system performance is analyzed under various constraints. Additionally, the paper explores the challenges associated with implementing hybrid scheduling in resource-constrained systems and proposes solutions to overcome them.